Methodology for Informational Base Preparation for Development of Preventive Measures and Threat to National Security Manageability - YERGAZIEV, Beibut; BAZAROV, Yerdan; AMANOV, Zhanybek; MAMONOV, Vassiliy; SMAILOVA, Urkiya (Journal of Advanced Research in Law and Economics, 2019)
These days, threats to national security are multiplicative. Effective responses to such threats require high-quality informational base, which is achieved through description, analysis and assessment of threats using appropriate methodology. Various approaches and methods for analyzing and assessing threats to national security are currently being applied in science and practice. General methods that do not allow comprehensive description and formation of a full picture of the threat are often proposed, or methods used only in one and not applicable to other spheres of social relations. The aim of this article is to develop unified, universal methodology for describing, analyzing and assessing threats to national security. The result of the study is Check-list, which allows to describe and assess the threat, as well as to determine the list and content of measures to be taken by public authorities in accordance with their functional purpose.